Avaliação da suscetibilidade à ocorrência de corridas de massa na bacia hidrográfica do Ribeirão Pau D'Alho, Caraguatatuba-SP - Demarchi, Flávia Beatriz [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
The debris flows are phenomena with great potential of destruction that causes a lot of social, economic and environmental losses all around the world. Many features are associated with these processes, but the geological-geotechnical features have more influence. Because of this, the geological-geotechnical mapping and the susceptibility evaluation of the debris flow occurrence are essential to the planning of warning and emergency projects. The main objective of this study is to evaluate the susceptibility of the Pau D'Alho River Basin through the physiographic features and land use analysis. At first, there was made the declivity map and the digital elevation model to support next stages. After that, the physiographic compartmentalization was made using photoanalysis and photointerpretation techniques, and the preliminary susceptibility was defined. The landslides scars were delimited and the land use classes were defined too. The natural and anthropic susceptibility maps were developed using Reis (2016) methodology, and it were integrated to find the total susceptibility of the area. Five physiographic units were recognized and delimited, and the units with most expressive occurrence in area are characterized with high declivity, wide topographic range, medium-high density of drainage and landform features, and concave hillsides, with many landslide scars. The photointerpretation of these features suggests medium-high debris flows susceptibility to the basin. The land use classes are too uniform, with prevalence of forest and grazing areas. In the evaluation stage, the natural susceptibility map showed more risk of debris flows in areas with high declivity, concave hillsides and high drain features. The anthropic susceptibility map showed low susceptibility according to land use classes. Integrating these two ... (Complete abstract electronic access below)

As corridas de massa são fenômenos de grande potencial destrutivo que causam muitos prejuízos sociais, econômicos e ambientais em todo o mundo. Diversos fatores podem estar associados a esses processos, entretanto há maior influência das características geológico-geotécnicas. Em decorrência disso, o mapeamento geológico-geotécnico e avaliação da suscetibilidade à ocorrência de corridas de massa nas bacias hidrográficas são essenciais para que possam ser elaborados planos preventivos e emergenciais a esses eventos. Nesse sentido, o principal objetivo do presente trabalho é avaliar a suscetibilidade da Bacia Hidrográfica do Ribeirão Pau D'Alho por meio da análise de atributos fisiográficos e de uso e ocupação do solo. A princípio foram elaborados o mapa de declividade e modelo digital de elevação a fim de auxiliar as etapas seguintes. Posteriormente, realizou-se a compartimentação fisiográfica da área através de técnicas de fotoanálise e fotointerpretação, onde foi possível a definição da suscetibilidade preliminar da bacia. Ainda nessa etapa, foram delimitadas as cicatrizes de escorregamento que ocorrem na área e também foram definidas as classes de uso e ocupação do solo. A partir da metodologia de Reis (2016) foram elaborados os mapas de suscetibilidade natural e suscetibilidade antrópica, posteriormente integrados para definição da suscetibilidade total. Foram reconhecidas e delimitadas cinco unidades fisiográficas, sendo que as mais expressivas na área se caracterizam por possuir alta declividade, grande amplitude, média a alta densidade de elementos de drenagem e relevo, e encostas de forma côncava a retilínea, além de representarem as áreas de ocorrências das cicatrizes de escorregamento. A fotointerpretação destes atributos sugeriu ... (Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Geomorfologia; Bacias hidrograficas; Deslizamentos (Geologia); Caraguatatuba (SP)